(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
In today’s sports world, technological advancements have significantly transformed the quality and effectiveness of training processes. In sports like badminton, which require speed and coordination, the integration of technology into coaching provides major advantages in terms of technical analysis, performance monitoring, and the creation of personalized training programs. This article examines the main technological tools and applications used in badminton coaching, evaluates their impact on athlete development, and offers suggestions for potential future uses.